IMPLEMENTASI PROBLEM BASED LEARNING DIDUKUNG MEDIA WIZER.ME UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA PADA MATERI ZAT ADITIF - Beta Puji Tria Agustin; Wahyu Budi Sabtiawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the effect of implementing the Problem-Based Learning (PBL) model supported by the Wizer.me media in improving students’ critical thinking skills on the topic of food additives, as well as to examine the learning implementation and students’ responses. The study was conducted in class VII E at SMPN 1 Paciran using a quantitative approach with a one-group pretest–posttest design. The instruments used included a critical thinking skills test, a response questionnaire, and an observation sheet for learning implementation. The data were analyzed using the N-Gain, normality test, and paired t-test. The N-Gain result was 0.53, indicating a moderate level of improvement. The paired t-test showed a significance value of less than 0.001, indicating that the learning had a significant effect. This is also supported by the learning implementation results, which reached 100%, and the student response results of 76.1%, categorized as positive. Based on these results, it can be concluded that the implemented learning shows an improvement in students’ critical thinking skills, with very good implementation and a fairly positive response.